Endoplasmic reticulum-targeted fluorogenic probe based on pyrimidine derivative for visualizing exogenous/endogenous H2S in living cells. (August 2020) - Wang, Hui; Hu, Lei; Xu, Bingsong; Chen, Hao; Cai, Fengze; Yang, Naidi; Wu, Qiong; Uvdal, Kajsa; Hu, Zhangjun; Li, Lin
Abstract: Developing new probes for visualizing H2 S in the endoplasmic reticulum (ER) is of great significance in physiological and pathological fields in that the probe can antagonise ER stress. Herein, we try to explore efficient reporting fluorophores based on three pyrimidine derivatives (L1, L2 and L3 ), and eventually, a novel probe WH2S was fabricated by using emissive pyrimidine derivative (L1 ) as the reporting fluorophore. Upon the addition of H2 S, the probe processed a thiolytic cleavage to regenerate L1, delivering a remarkable fluorescence enhancement. Probe WH2S presents a perfect selectivity, high sensitivity and low detection limit (3.81 μM) towards H2 S in the buffer media. Most importantly, fluorescence microscopy experiments demonstrate that WH2S can precisely accumulate in ER and detect exogenous/endogenous H2 S at cellular level. These results imply that probe WH2S possesses great potentiality in tracking target H2 S in complicated and changeable living systems. Graphical abstract: Image 1 Highlights: Probe for specific detecting H2 S has been developed based on fluorophore incorporated with thiolytic cleavable war head. The results demonstrated it could visualize endoplasmic reticulum H2 S in live cells with a high Rr of 0.92. The application of the probe in visualizing cysteine-induced endogenous H2 S at the cellular level was successfully achieved vi a confocal fluorescence imaging.